Patterns of Cultural and Coping Factors Among Minoritized Youth: Associations with Discrimination and Depressive Symptoms - Christophe, N. Keita (Race and social problems, 2024)
Models of resilience in minoritized youth posit that youth need to draw upon multiple different cultural (e.g., identity, values, etc.) and general factors (e.g., coping) to thrive in the face of discrimination. Nonetheless, the integration of these factors in empirical scholarship is lacking, as scholars have typically focused on single factors within these models in isolation. To provide a more holistic test of these theoretical models, we utilized latent profile analysis, a technique well-suited to examine the simultaneous impact of multiple factors, to identify patterns of cultural promotive factors (ethnic-racial identity, religious coping, and familism) and a general coping factor (shift-&-persist) in 694 minoritized (Mage = 17.24, 73.5% women, 46.1% black) youth. We observed four profiles: High Cultural High Coping, Average Cultural Average Coping, Low Religious Low Coping, and Low Cultural Low Coping. Despite a lack of developmental differences, several profile differences emerged with respect to gender, race, and socioeconomic status. Additionally, Average Promotive Average Coping youth experienced the greatest amount of discrimination. Finally, after accounting for the effects of discrimination and covariates, those in the High Cultural High Coping profile displayed fewer depressive symptoms than those in the Average Cultural Average Coping and Low Religious Low Coping profiles.